Sense of Solidarity in Sarojini Naidu Poem's: Exploring Sarojini Naidu's Unique Nature Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Sarojini's love of nature is reflected even in sonnets which are not about nature, but rather havean alternate subject. Her reaction to Nature is straight forward and guiltless like that of a kid who takes agander at nature with interest and is hit with wonder by her greatness and mystery. Her nature poetry ismost certainly set apart with two kinds of states of mind. In her prior nature sonnets she enjoys the tripof extravagant and bounty of creative mind. In the later sonnets managing Nature, we have theprofundity of feeling, a brilliant way of thinking of life which hates death and competes with eternality.Sexiness is the transcendent nature of her nature poetry. Every one of the feelings of touch, smell, eyeand others are evoked, incited and fulfilled. As a genuine craftsman, Sarojini conveys her ideaunequivocally, pleasantly and beautifully. She has chosen words cautiously both concerning their senseand sound. This unmistakable and unique kind of her phrasing is represented in various ways.